2019
DOI: 10.1371/journal.pone.0216925
|View full text |Cite
|
Sign up to set email alerts
|

Nagaland health assessment: High mortality rates and difficulty accessing essential health services in Lahe Township, Republic of the Union of Myanmar

Abstract: Introduction Lahe Township belongs to Myanmar`s Naga Self-administered Zone, which is one of the most remote and mountainous areas in Myanmar. However, the limited health data available for the region suggests that there could be neglected health needs that require attention. The purpose of this study was to assess the health status of the population of Lahe Township. Methods A cross-sectional study design incorporating a two-stage cluster sampling methodology recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…, 2016; Ei et al. , 2019; Oo et al., 2021). One study reviewed the oral healthcare system in Myanmar using six building blocks and found low utilisation of oral healthcare services, lack of workforce, inadequate budget with non-transparent expenditure, and insufficient supply (Saw et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2016; Ei et al. , 2019; Oo et al., 2021). One study reviewed the oral healthcare system in Myanmar using six building blocks and found low utilisation of oral healthcare services, lack of workforce, inadequate budget with non-transparent expenditure, and insufficient supply (Saw et al.…”
Section: Discussionmentioning
confidence: 99%
“…Complementando, em estudo realizado em Lahe Township, Myanmar, Ásia, em 97 aldeias, a pobreza é um fator que contribui como barreira para o acesso aos serviços de saúde, devido aos custos e falta e/ou dificuldade de conseguir transporte para se deslocar até a unidade de saúde. Além da longa distância, enfrentam também a distribuição desigual da infraestrutura para transporte, tendo número limitado de estradas e condições do terreno perigosas, de modo que as aldeias tornam-se inacessíveis durante chuvas fortes (30) .…”
Section: "Por Ser Um Longo Percurso Até Chegar Ao Hospital Eu Peço Ao...unclassified
“…The choice of place of birth is very important to study, because in areas that have limited access to delivery services in health facilities, tend to be followed by high cases of maternal mortality (Ei et al, 2019) (Macuácua et al, 2019) (Cockcroft et al, 2019). Based on the background, this article was compiled to analyze urban-rural disparities of facility-based childbirth in Indonesia.…”
Section: Introductionmentioning
confidence: 99%